Replication of The Morning After: Report from the Nottingham Replication Games - Christian Oswald; Julian Walterskirchen; Sonja Häffner; Marco Binetti; Christoph Dworschak (Institute for Replication (I4R), 2023)
We replicate the analysis provided in Bokobza et al. (2022). They identify a causal effect of failed coup attempts on cabinet minister removals in autocracies on both the country and individual minister level and show that higher-ranking ministers and those holding strategic positions are more likely to be purged than more loyal and veteran ministers using fixed effects panel models. We focus on computational reproducibility and robustness replicability. In addition to reproducing the original results using Stata and R, we replicate analyses using random effects panel models and ordered beta regression models, reproduced analyses performed in R using different packages, replaced the main independent variable, clustered standard errors on a different level, and added independent variables related to coup-proofing. We find that the original findings were reproducible and robust.
Keywords: 330